2013
DOI: 10.2298/mpns1310387m
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of the proximal tibiofibular joint

Abstract: The proximal tibiofibular joint dislocation may be the cause of the chronic pain of the knee so it has to be taken into account when making differential diagnosis in case of the pain at the lateral side of the knee. The key for making the accurate diagnosis is the technically correct X-ray of the injured knee compared with the opposite one, showing the displacement of fibular head. If manual reposition fails, open reduction internal fixation and screw transfixation of the proximal tibiofibular joint allow good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Although a number of case reports exist describing traumatic proximal tibiofibular dislocation (PTFD) in association with extremity trauma, 2,6,7,9 there are no series examining PTFD because it relates to high-energy traumatic injuries to the lower extremity apart from 1 report in the French literature by Garion et al 8 describing 9 cases. Currently, the majority of the literature focuses on sports-related injury to the proximal tibiofibular joint with the largest series published by Ogden in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Although a number of case reports exist describing traumatic proximal tibiofibular dislocation (PTFD) in association with extremity trauma, 2,6,7,9 there are no series examining PTFD because it relates to high-energy traumatic injuries to the lower extremity apart from 1 report in the French literature by Garion et al 8 describing 9 cases. Currently, the majority of the literature focuses on sports-related injury to the proximal tibiofibular joint with the largest series published by Ogden in 1974.…”
Section: Introductionmentioning
confidence: 99%
“…When the knee is in extension the fibular head goes backward, pulled by LCL and femoral biceps tandon, so the ligament produces stability in the extended knee [16]. Coobs et al [1], LaPrade et al [9] and Buzzi et al [17] have shown that only an anatomical LCL reconstruction can restore the near normal knee stability after LCL tears.…”
Section: Discussionmentioning
confidence: 99%
“…If closed reduction fails, as it was in the presented case, ORIF will be performed with K-wires or screws 9,10 . In our case the PTFJ was transfixed with one cortical screw with canvas, through three bone cortices.…”
Section: Disscusionmentioning
confidence: 98%
“…After six weeks we took out the screw although it is recommended after 3-6 months 33 , because we wanted to avoid cracking the screws as it was in two cases. Some authors also removed the screw after six weeks 10 . In the presented case full weight bearing was given immediately after removing the screw, but without the previously placed postoperatively immobilization which resulted in faster patient recovery and his earlier return to sports activities.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation